Internalization of Democracy Values Through Proyek Pengutan Profil Pelajar Pancasila to Determine Radicalism in Adolescents - Muhammad Qomaruddin Sya'bani; Citra Fitri Kholidya (Edutechnium Journal of Educational Technology, 2023)
The purpose of this study was to find out the implementation of the Pancasila Student Profile Project (P5) activities and the internalization of democratic values in order to ward off radicalism among teenagers, especially students at SMKN 1 Kemlagi. The method used is descriptive qualitative using a case study approach. Primary data sources or informants are the Principal of SMKN 1 Kemlagi, the Head of P5, the Project Facilitator, and representatives of class X students. Meanwhile, secondary data sources are project modules, student worksheets, and facilitator journals. Data collection techniques in this study used in-depth interviews, observation, documentation, and a literature study. Miles and Huberman developed data analysis techniques for data collection, reduction, presentation, and conclusion. The results of this research are: 1) the implementation of P5 activities at SMKN 1 Kemlagi is carried out in four stages. First, the introduction stage by inviting parties from the KPU Kab. Mojokerto. Second, contextualization by participating in the election of the OSIS chairman for the 2022-2023 period. Third, in the action stage, students plan to carry out general elections with a theme according to their individual choices. Fourth, in the presentation and reflection stage, students present the project results to all parties involved. 2) internalization of democratic values through P5, including values of tolerance, values of freedom, values of cooperation, and values of justice.